Efektivitas Pelaksanaan Program Rehabilitasi dan Rekonstruksi Sektor Permukiman Pascabencana Gempabumi di Pulau Lombok - Embun Suryani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to evaluate the effectiveness of post-disaster recovery and physical improvement activities and identify obstacles and problems faced. The study was conducted in 5 districts/cities affected by the earthquake on Lombok Island in 2018. The key informants in this study were BPBDs in the affected districts/cities, along with facilitators for each area. Data collection techniques used was interviews and observation. The effectiveness test was carried out based on the 5T standards set by BNPB, namely the right planning, right administration, right budget absorption, right technical specifics and on time. The results of data analysis indicate that the implementation of the Phase I RTG can be categorized as not meeting 5 standards: 1) not "Appropriate Planning"; 2) not “Proper administration”; 3) enough "Appropriate Budget Absorption"; 4) "Exactly technically specific",; and 5) not “On time”. On the other hand, evaluation of the implementation of the Phase II RTG can be categorized as proper planning, proper administration, proper absorption of the budget, precise technical specifications, and on time. This is because the implementation of the Phase II RTG was carried out in conditions that did not respond to an emergency and were small in number. It is concluded that all regencies/cities can implement this Phase II RTG in accordance with all established standards.